Colonial racialism is the cause of the conflict in eastern DRC, not minerals - Rutazibwa, Privat (ResearchGate, 2025)
The American NGO IRC (International Rescue Committee) and the UN Group of Experts on the Illegal Exploitation of Natural Resources and other Forms of Wealth in the Democratic Republic of Congo created by the UN in 2000 'under pressure from French diplomacy' contributed immensely in imposing the negationist narrative of the exploitation of Congolese minerals as the cause of the conflict and extreme violence, and this narrative succeeded in replacing the indignation aroused until then by the genocide perpetrated against the Tutsi in 1994 in Rwanda and its persistent threats. It's horrifying to see how the international community is concerned about protecting and defending the minerals of the DRC, while displaying a monstrous insensitivity in the face of people who are systematically persecuted, who are tortured, who are killed and whose flesh is eaten in broad daylight and in front of the cameras, simply because they are of Tutsi origin or suspected of being such. The first genocide against the Tutsi committed by Belgium from 1959 was whitewashed into 'social revolution' and many Western knowledge producers in the media and even in the research community have normalized it to this day. I have referred to this latter category in my previous articles as 'criminal scholars'. The persistent genocidal attacks and threats against Rwanda and the Congolese Batutsi since 1994 to date are equally whitewashed as false pretexts to conceal the expansionist and predatory ambitions of a phantasmagoric Hima-Tutsi empire allegedly 'in the pay of Western imperialists', and the same Western knowledge producers validate the narrative; whether mainstream media, UN experts or so-called researchers. Colonial racialism is the cause of the conflict in eastern DRC, not minerals. There has always been a permanent threat from Westerners to destroy all effective and genuine African governance on the continent using Africans who chose to adhere to the colonial ideology of antagonistic African ‘races’. If they were reasonable, Westerners should also stop blackmailing Rwanda with aid and instead think about reparations. Rwanda does not need to demand this reparation. It has rebuilt itself and will rebuild itself with or without it. On the other hand, these Western countries and organizations need to take this action for their own redemption.
Keywords: Colonial racialism; DRC; Rwanda; UN